If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 5b + -1a = 0 Reorder the terms: 3a + -1a + 5b = 0 Combine like terms: 3a + -1a = 2a 2a + 5b = 0 Solving 2a + 5b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5b' to each side of the equation. 2a + 5b + -5b = 0 + -5b Combine like terms: 5b + -5b = 0 2a + 0 = 0 + -5b 2a = 0 + -5b Remove the zero: 2a = -5b Divide each side by '2'. a = -2.5b Simplifying a = -2.5b
| -(5x-4y+9z)= | | 14-x=6-x | | .5/32= | | (11-x)-3=2 | | 3x+9-15+5x=12x-6-4x+9 | | -2/288= | | 1/2/32= | | X-3x/5=2/3 | | 1/2^32= | | tan(2x)-2x=0 | | 9t-12=5t | | y*(y*y)= | | y*ysquared= | | 3x^2/3=0 | | 10x-4=6x-28 | | x-10=-x-20 | | x+x=1505.94 | | 2x+16=-x+37 | | 0.35X^2-0.753X-21.6=0 | | -3x+5=-2x+4 | | 0.35X^2-0.753X-21.6=02 | | 0.35X^2*0.753X-21.6=02 | | -9x-1=-5x+3 | | -7x+11=-3x+19 | | -5x+11=-x-25 | | -3x-17=-14 | | 6x+14=3x+2 | | 13x+22=6x+71 | | 7x+18=4x+48 | | 2x+21=x+20 | | 8(t-3)+7t=5(3t+3)-10 | | 2y+3y=0 |